TEACHING UKRAINIAN AS A FOREIGN LANGUAGE BY USING MIND MAPPING TECHNIQUE - Leshchenko, Tetyana; Zhovnir, Maryna; Grinko, Natalia (Educological discourse, 2021)
The article is devoted to the problem of successful implementation of different cutting-edge techniques in teaching in the context of the current significant modifications and profound transformations of the educational system in Ukraine. This work focuses on the forming a foreign medical student linguistic personality, in particular it’s grammar, speech, communication as well as socio-cultural competencies, including by utilizing Advanced Information and Communication technology tools. This research focuses on the introduction of Advanced Information and Communication Technologies into the Ukrainian educational process. It was pointed out, that the effective teaching methodology could be based on the newest methods and techniques. The advantages of pedagogical innovation in comparison with traditional methods of presenting educational information was pointed out. The researchers have interpreted the term Mind map. They have also presented and analyzed its important features, common ways of implementation into current teaching process.